Crystal structure of (Z)-4-(((4-bromophenyl)amino)(furan-2-yl)methylene)-2,5-diphenyl-2,4-dihydro-3H-pyrazol-3-one, C26H18BrN3O2 - Li Zhang; Wu Qiong; Zhang Ya-Zhai; Zhang Wei-Ya; Chen Hong-Li; Zhang Heng-Qiang (Zeitschrift für Kristallographie - New Crystal Structures)
C26H18BrN3O2, monoclinic, P21/n (no. 14), a = 9.5191(14) Å, b = 23.056(3) Å, c = 10.0556(15) Å, β = 95.470(3)°, V = 2196.9(6) Å3, Z = 4, Rgt(F) = 0.0640, wRref(F2) = 0.1645, T = 296(2) K.